Legalization Of Abortion Against Victims Of Rape Crimes Viewed From Victimology Perspective - Elvandari, Siska (Jurnal Hukum & Pembangunan, 2020)
One of human rights guaranteed and protected in the 1945 Constitution is the right to live and maintain life, stated in Article 28 A of the 1945 Constitution. The right to live and maintain life is the highest right that is inherent in human beings as the subject of law since humans were born to death in the world. The right to live and maintain life is not only inherent in human beings who have been born, but also in humans or children who are still in the womb, stated in Article II of the Civil Code that "Children are considered to have been born when interest is desired. However, in fact the guarantee and protection of the right to live and maintain life has been neglected in line with the legalization of abortion against victims of rape crimes stated in Law Number 36 Year 2009 concerning health. The legalization of abortion against victims of rape crimes certainly has drawn polemics in various circles, namely between pro life and pro choice groups.